Bina Projelerinin Yangın Ve Güvenlik Bakımlarından Değerlendirilmesi - Yeğiner, A. Aylin (Fen Bilimleri Enstitüsü, 1995)
Dünyada hayatın başlaması ile güvenlik problemi de başlamıştır. İnsanlar doğadan ve diğer canlılardan sakınmaya çalışmış, daha sonra problem artınca da önlemler almaya başlamışlardır. Gelişen dünya güvenlik ve yangın problemlerini çözememişlerdir. Bu problemler her zaman çözümlerin önünde gitmektedir. Günümüzde güvenlik probleminin iş sırları, bilgi hırsızlığı, anarşi, terör gibi çok değişik yönlerde da ha da büyüdüğü açıkça görülmektedir. Yangın olaylarının yol açtığı maddi zararlar da alınan bütün önlemlere rağmen giderek artmaktadır. Mimarlara bu problemlerin çözülmesinde çok büyük görev düşmektedir. Bir binanı tasarım ve inşaat aşamalarında yangın ve güvenlik ekipmanlarının iyi değerlendiril meleri ve uygun yerleştirilmeleri, iyi derecede koruma sağlayacaktır. Bu da mimarın başarısıdır. Bu nedenle bina içi muhtemel yangın ve güvenlik problemlerinin ve bunlar için kullanılacak koruma sistemlerinin bilinmesi, bunların daha proje aşamasında değerlendirilmesi, gereken en uygun araçların seçilerek en iyi şekilde yerleştirilmesi gerekir. Planlama bunları sağlayacak yönde geliştirilir. Bu konulardaki değerlendirmenin sağlam bilimsel temellere dayanması gerekir. Bu nedenle tezde bilimsel değerlendirme teknikleri irdelenmiş, sonucunda bu çalışma için rehber metodunun uygulanması uygun görülmüştür. Tezde ele alınan güvenlik ve yangın önlemlerinin binalardaki değerlendirilmesi sekiz başlık altında ele alınmaktadır; değerlendirme kriterleri, metod seçimi, önlemlerin binadaki yerleşimle ri, malzemelerin, tesisatların, ekipmanların seçimi, planların hazırlanması, binada eşya yerleşimi, ölçülerin kesinleştirilmesi ve dokümantasyon. Bu başlıklar altında dikkat edilmesi gereken kriterler sıralanmıştır ve ana bilgiler hatırlatılmıştır. Rehber önerisinden sonra, daha detaylı bilgilerin bulunduğu eklerde ise, güvenlik ve yangın korunumu için kullanılan araç ve tesisatların özellikleri ve şekilleri verilmektedir. Çalışma proje aşamasında yangın ve güvenlik konusunda kendi kendine değerlendirme yapmak isteyecek mimarlara, kullanımı kolay, pratik bir yardımcı sunmakta dır.

Safety and shelter are among main reasons for man's urge to built and in many circumstances it is abvious that safety is the most vital requirement. Security in its broadest meaning involves man's confidence in the safety and privacy of his environment. Physical safety from fire or other hazards in a building is as commonly appreciated as is the loss incurred when possessions are stolen or damaged. However psychological shock sustained by occupants of a burnt or burgled building must also be borne in mind, as must tensions resulting from infringement of privacy. The latter can arise from being overlooked or overheard also might be regarded as a "territorial" instinct in animals. New conditions intensify the problems. Industrial processes are more extensive and consume more energy. These lead to greater fire risk which can destroy more lives and property than before owing to dansities of occupancy and concentrations of value in modern buildings. New means of mobility enable stolen goods to be marketed and thieves to escape. Extensive research and valuable new processes give scope to thase thieves of ideas the industrial spies. For example thousands of man hours and lots of money may be required to develop a pharmaceutical product, yet the formula is kept on only one piece of paper. Increasing populations and curiosity cultivated by popular comunications media, put personal privacy at a premium. This is at a time when eaves droppers are aided by directional microphones, radio equipment and tape recorders, and peeping toms by telephoto lences, closed circuit TV, video recorders and infra-red photography. In these circumstances, having nothing to hide is a defence unfortunately available to very few. Indeed, defence must be complex and efficient. Planning and protective devices must be effective without destroying the quality of life of these living is working in secure conditions. This is a design problem in the first order. Historically the architect has always been concerned with "secure" buildings and military engineering. These were an essential part of the medieval mason. Leonardo da Vinci prepared designs for veapons and eighteenth century town planners considered defence and internal security important in their designs. Aesthetic consequences of security were not ignored. Grilles on the ground floor windows of Italian Renaissance palaces were essential and the walls and fances of Dolmabahçe Palace are in effect a security fence. The safety of a client, his employees, his building and belongins are an essential part of an architect's responsibility. This is less vital now when police forces and fire brigodes have partly relieved individuals of the necessity to protect their own property. But lighter construction and architects tendency to impose "ideal"
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Binalar; Güvenlik analizi; Proje değerlendirme; Yangın; Buildings ;Safety analysis ;Project evaluation ;Fire